2010
DOI: 10.1007/s10709-010-9472-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and connectivity remain high in Holothuria polii (Delle Chiaje 1823) across a coastal lagoon-open sea environmental gradient

Abstract: Coastal lagoons represent habitats with widely heterogeneous environmental conditions, particularly as regards salinity and temperature, which fluctuate in both space and time. These characteristics suggest that physical and ecological factors could contribute to the genetic divergence among populations occurring in coastal lagoon and open-coast environments. This study investigates the genetic structure of Holothuria polii at a micro-geographic scale across the Mar Menor coastal lagoon and nearby marine areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 78 publications
4
47
0
1
Order By: Relevance
“…As P. marmoratus is associated with brackish and hyper-saline habitats, which are systems suffering frequent environmental fluctuations and disturbances, this species could have been exposed to extreme conditions more frequently than other marine species inhabiting open sea habitats. Our results point a significant link between extreme lagoonal environmental conditions (mainly maximum salinity) and genetic composition, such as it was already demonstrated on cockles and sea cucumbers populations from the Mar Menor lagoon (González-Wangüemert et al 2009;Vergara-Chen et al 2010b). This find is very interesting because previously several authors had defined different ecological requirements for the various Pomatochistus species; for example, P. marmoratus survives to higher salinities than P. microps, especially in habitats whose temperature and salinity change through the year, but do not vary abruptly (Berrebi et al 2005).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As P. marmoratus is associated with brackish and hyper-saline habitats, which are systems suffering frequent environmental fluctuations and disturbances, this species could have been exposed to extreme conditions more frequently than other marine species inhabiting open sea habitats. Our results point a significant link between extreme lagoonal environmental conditions (mainly maximum salinity) and genetic composition, such as it was already demonstrated on cockles and sea cucumbers populations from the Mar Menor lagoon (González-Wangüemert et al 2009;Vergara-Chen et al 2010b). This find is very interesting because previously several authors had defined different ecological requirements for the various Pomatochistus species; for example, P. marmoratus survives to higher salinities than P. microps, especially in habitats whose temperature and salinity change through the year, but do not vary abruptly (Berrebi et al 2005).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, the lack of significance in the AMOVA comparisons between groups could be also due to low power associate with a low number of populations per group such as was described by Fitzpatrick (2009). Therefore, according to our results from F ST values, Cavalli-Sforza genetic distances, correspondence analysis and significant genic and genotypic differentiation, we suggested that the highest genetic divergence observed between samples (Mazarrón and the rest of localities) could be consequence of the isolation of lagoonal populations from open sea which has been already reported in other coastal fishes such as Pomatoschistus minutus Berrebi et al 2009), Dicentrarchus labrax (Lemaire et al 2000), Atherina lagunae (Trabelsi et al 2004), Atherina boyeri (Kraitsek et al 2008;Milana et al 2012), Diplodus sargus (González-Wangüemert and Pérez-Ruzafa 2012) and several invertebrate species (Camilli et al 2001;González-Wangüemert et al 2006;Tarnowska et al 2010;Vergara-Chen et al 2010b).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The high number of exclusive haplotypes showed in Kusadasi area may increase their fitness under unusual conditions (Ryman et al, 1995;Pérez-Ruzafa et al, 2006;Vergara-Chen et al, 2010;González-Wangüemert & Vergara-Chen, 2014). That genetic diversity could provide the raw material for the maintenance of the diversity longer evolutionary time-scales and may also confer the basis for adaptation to environmental change (Sanford & Kelly, 2011;González-Wangüemert & Vergara-Chen, 2014).…”
Section: Genetic Diversity and Effects Of Mpasmentioning
confidence: 99%
“…According previous genetic studies carried out on sea cucumbers (Vergara-Chen et al, 2010;Borrero-Pérez et al, 2011;González-Wangüemert & Borrero-Pérez, 2012;Valente et al, 2014), a representative number of individuals from each locality were analyzed. DNA extractions were done based on Sambrook et al (1989) protocol.…”
Section: Genetic Analysismentioning
confidence: 99%